The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis